Critical geographies of sport: space, power and sport in global perspective - Koch, Natalie (Routledge critical studies in sport, 2017)
Introduction : critical geographies of sport in global perspective / Natalie Koch -- Geopolitics, identity, and horse sports in Finland / Pauliina Raento -- Spreading the game or reproducing hegemony? : the United States and the regional geopolitics of women's football in the Americas / Jon Bohland -- Nation-building and sporting spectacles in authoritarian regimes : Turkmenistan's Aziada-2017 / Slavomír Horák -- Sports and politics in Israel : settler colonialism and the native Palestinians / Magid Shihade -- Sports fields and corporate governmentality : Gazprom's all-Russian gas program as energopower / Veli-Pekka Tynkkynen -- Athletic autocrats : understanding images of authoritarian leaders as sportsmen / Natalie Koch -- Playing identity politics : the Gaelic Athletic Association in modern Ireland / Arlene Crampsie -- Soccer and the mundane politics of belonging : Latino immigrants, recreation, and spaces of exclusion in the rural US South / Lise Nelson -- Competing visions for urban space in Seoul : understanding the demolition of Korea's Dongdaemun Baseball Stadium / Jung Woo Lee -- Running order : urban public space, everyday citizenship and sporting subjectivities / Simon Cook, Jon Shaw, Paul Simpson -- Mallparks and the symbolic reconstruction of urban space / Michael Friedman -- Sports and the social integration of migrants in South Dublin / Neil Conner -- Spatial maneuvers : geographies of power and labor practices in professional wrestling's territorial era / Bradley Gardener -- In the shadow of mega-events : the value of ethnography in sports geography / Nicholas Wise -- Conclusion : toward a critical geography of sport : space, power, and social justice / David Jansson and Natalie Koch